Tom's Struggle For Love In 500 Days Of Summer: An Humanistic Psychological Perspective - Diyanti, Salistia Rohma; Nugroho, Abdillah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research uses Abraham Maslow's (1954) humanistic theory to examine Tom's struggle for love in the movie "500 Days of Summer" from a personal psychology standpoint. The study looks into how Tom's emotional journey, interpersonal relationships, and romantic problems are portrayed in the film. The analysis looks at significant conversations, scenes, and psychological facets of Tom's character using a qualitative methodology. The findings show that Maslow's hierarchy of requirements, which places a strong emphasis on social connection and self-actualization, is in line with Tom's struggle for love. The impact of Tom's romantic struggles on day-to-day living is also covered in the study, eliciting thoughtful comments on interpersonal connections, perspectives on love, and emotional fortitude. All things considered, "500 Days of Summer" provides not just a sophisticated love tale but also a window into the protagonist's emotional and psychological development.